2016
DOI: 10.1177/1533034615597366
|View full text |Cite
|
Sign up to set email alerts
|

PI3K Inhibitor Combined With Chemotherapy Can Enhance the Apoptosis of Neuroblastoma Cells In Vitro and In Vivo

Abstract: Activation of the phosphoinositide 3-kinase (PI3K)/Akt signaling pathway is a novel poor prognostic indicator of neuroblastoma (NB), and the positive effects of chemotherapy on NB have been confirmed. In this study, we investigated the effect of small molecule PI3K inhibitor PI103 on chemosensitivity. The PI3K inhibitor cooperates with doxorubicin to synergistically induce apoptosis and to reduce tumor growth of NB in in vitro and in vivo models. Human NB cells, SH-SY5Y and SK-N-BE(2), were treated with PI103 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The AKT survival pathway is activated as part of the cellular survival response against doxorubicin treatment [43,44]. Indeed, studies have demonstrated the effectiveness of inhibiting doxorubicin-induced AKT activity to improve the response to doxorubicin [27,55,56]. In addition, increased activation of AKT has also been associated with chemoresistance in MC, including to doxorubicin, and inhibition of AKT activity reverses the resistance [43,57,58].…”
Section: Discussionmentioning
confidence: 99%
“…The AKT survival pathway is activated as part of the cellular survival response against doxorubicin treatment [43,44]. Indeed, studies have demonstrated the effectiveness of inhibiting doxorubicin-induced AKT activity to improve the response to doxorubicin [27,55,56]. In addition, increased activation of AKT has also been associated with chemoresistance in MC, including to doxorubicin, and inhibition of AKT activity reverses the resistance [43,57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Chemoresistance of DOX is a complex process involving the regulation of many cellular biology processes through various mechanisms, including increased expression of p-glycoprotein efflux transporter protein [7, 8]. Many studies have suggested that inhibition of the PI3K/AKT and NF-κB pathways plays an important role in improving the effectiveness of DOX [9,10]. The PI3K/AKT pathway plays a crucial role in cell proliferation, survival, and drug resistance through regulating multiple downstream cascades in various cancers, including PC cells [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…When the tumors reached palpable size (about 100mm 3 ), there were two groups of mice were started to receive intraperitoneal injection with the doxorubicin (1 mg/kg/every 3 days). The other two groups were received PBS intraperitoneal injection as negative control, the reference for the dose and course of treatment of doxorubicin can be found in Stewart’s and Geng’s work [ 16 , 17 ]. Eight weeks after Chemotherapy, mice were sacrificed and tumor xenografts were removed, weighed, and fixed in formalin for HE and IHC staining.…”
Section: Methodsmentioning
confidence: 99%